Myeloid-derived suppressor cells: mechanisms of action and recent advances in their role in transplant tolerance - Dilek, Nahzli; Vuillefroy de Silly, Romain; Blancho, Gilles; Vanhove, Bernard (Frontiers in Immunology, 2012)
Myeloid derived suppressor cells (MDSC) are a heterogeneous population of immature hematopoietic precursors known to suppress immune responses in infection, chronic inflammation, cancer and autoimmunity. In this paper we review recent findings detailing their mode of action and discuss recent reports that suggest that MDSC are also expanded during transplantation and that modulation of MDSC can participate in preventing graft rejection.